Answer:
.
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
Answer:
n4ur84234r
Step-by-step explanation:
3874rfbh dc
Answer: You can multiply the top equation by -1 to eliminate the x variable.
And the solution is (2,4/3) in case you need it.
Step-by-step explanation:
2x + 3y = 8
2x + 6y = 12
If you multiply the upper equation or down equation by one, you will be able to eliminate the x variable.
-1( 2x + 3y) = -1(8) New equation: -2x -3y = -8.
Add the new equation you got by multiplying the top equation by -1 to the bottom equation.
Add them: -2x -3y = -8
2x + 6y = 12
3y = 4
y = 4/3
You can now input the value for y into the one of the equations and solve for x.
-2x - 3(4/3) = -8
-2x -4 = -8
+4 +4
-2x = -4
x = 2
Answer:
2
Step-by-step explanation:
r(x) = 2 sqrt(x)
s(x) = sqrt(x)
r(x) / s(x) = 2 sqrt(x) / sqrt(x)
= 2